Analysis of the Correlation Between Cases and Deaths of COVID-19 and Atmospheric Pollution (PM2.5) in Brazil - Carniel, Alessandra dos Santos; Guimarães da Silva, Mateus; Ribeiro Marques, Gilcinieri (Anuário do Instituto de Geociências, 2024)
The main route of the spread of novel coronavirus occurs through direct close contact with infected persons and with surfaces containing the virus. Breathing and speech also release smaller particles which remain in the air longer and can settle in particulate matter dispersed in the atmosphere and reach long distances, becoming a secondary source of virus transmission. Considering that Brazil has been recording concentrations of particulate matter above the value recommended by the World Health Organization, and the high numbers of deaths in COVID-19. In this study, the correlation between the concentration of PM2.5 and the number of occurrences of COVID-19 and daily deaths in the cities of the states of Acre and São Paulo were investigated. The results showed that there was a correlation in three of the twenty analyzes carried out with a confidence interval of 95%, being that the correlation coefficients were weak. Thus, it was not possible to assert a correlation and causality between the particulate material and the number of records of cases and deaths in COVID-19. It is noteworthy that other variables directly related to the transmission and proliferation of the virus, such as social distance and the use of masks, have been neglected in Brazil since the beginning of the pandemic. Although there is no proof of virus transmissibility through PM2.5, they can make the population more susceptible to contract the virus and die, as long-term exposure to these pollutants weakens the immune system, making the body difficult to cope with infectious agents.